The longitudinal influence of cyberbullying victimization on depression, self-esteem and academic burnout among Chinese adolescents: mindfulness as a mediator - Lu, Yanping; Dang, Longxin; Tao, Yuan (Frontiers in Psychiatry, 2025)
Cyberbullying victimization (CV) has been linked to numerous adverse psychological outcomes among adolescents. While previous research has established associations between CV and negative outcomes including depression, diminished self-esteem, and academic burnout, the potential protective mechanisms in these relationships remain underexplored. This longitudinal study investigated the mediating role of mindfulness in the relationships between CV and these psychological outcomes among Chinese adolescents. A sample of 1,421 Chinese high school students participated in this study. The participants were asked to complete self-report measures of CV, mindfulness, depression, self-esteem, and academic burnout at two time points, approximately six months apart. Structural equation modeling revealed that mindfulness partially mediated the relationship between CV and both depression and academic burnout. Mindfulness fully mediated the relationship between CV and self-esteem. The results highlight the potential value of mindfulness-based interventions in school settings to mitigate the detrimental effects of CV. Limitations of the current investigation and directions for future research and intervention development are discussed.